2004
DOI: 10.1101/gr.2246704
|View full text |Cite
|
Sign up to set email alerts
|

Compositional Gene Landscapes in Vertebrates

Abstract: The existence of a well conserved linear relationship between GC levels of genes' second and third codon positions (GC2, GC3) prompted us to focus on the landscape, or joint distribution, spanned by these two variables. In human, well curated coding sequences now cover at least 15%-30% of the estimated total gene set. Our analysis of the landscape defined by this gene set revealed not only the well documented linear crest, but also the presence of several peaks and valleys along that crest, a property that was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 39 publications
(41 reference statements)
0
10
0
Order By: Relevance
“…Indeed, scanning base composition along the DNA sequences of human chromosomes revealed regions that 1) exhibit a fairly homogeneous base composition ([ 14 , 16 ]; see also S1 Table ); 2) range from 200 Kb to several megabases [ 14 , 16 ]; 3) fall into five families, L1, L2, H1, H2 and H3 ([ 9 ]; also supported by the multimodal distribution of coding sequences [ 17 ]); 4) are flanked by sequences showing higher or lower GC levels, that generally belong to the compositionally closest families, so forming an ordered compositional mosaic; and 5) correspond to the families originally detected by ultracentrifugation [ 6 , 14 , 16 ]. The five isochore families are characterized by 1) increasing GC levels and GC ranges and decreasing average sizes ([ 16 ]; see Fig 1B and S1 Table ); 2) different trinucleotide frequencies [ 18 , 19 ] and different nucleosome positioning patterns [ 20 ]; 3) increasing gene densities [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, scanning base composition along the DNA sequences of human chromosomes revealed regions that 1) exhibit a fairly homogeneous base composition ([ 14 , 16 ]; see also S1 Table ); 2) range from 200 Kb to several megabases [ 14 , 16 ]; 3) fall into five families, L1, L2, H1, H2 and H3 ([ 9 ]; also supported by the multimodal distribution of coding sequences [ 17 ]); 4) are flanked by sequences showing higher or lower GC levels, that generally belong to the compositionally closest families, so forming an ordered compositional mosaic; and 5) correspond to the families originally detected by ultracentrifugation [ 6 , 14 , 16 ]. The five isochore families are characterized by 1) increasing GC levels and GC ranges and decreasing average sizes ([ 16 ]; see Fig 1B and S1 Table ); 2) different trinucleotide frequencies [ 18 , 19 ] and different nucleosome positioning patterns [ 20 ]; 3) increasing gene densities [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…This fact also explains why GC distributions of fixed-length fragments of the human genome (Lander et al 2001) do not show the local maxima observed here. Finally, the isochore families corresponded to peaks in "gene landscapes" (Cruvellier et al 2004), formed by the distribution of coding sequences according to the GC levels of second and third codon positions (GC 2 and GC 3 ).…”
Section: Isochore Familiesmentioning
confidence: 99%
“…This principle is often overlooked, despite much attention to automating gene prediction. In previous work, we proposed a simple screen, and applied it to rice [3,4], based on a constraint that is experienced by protein-coding genes in species ranging from human to Escherichia coli. GC levels (guanine 1 cytosine %) are distinctly lower in second (GC2) than in third (GC3) codon positions.…”
mentioning
confidence: 99%